The stigmatization of HIV-positive women and the role of associations of people living with HIV/AIDS (APWA) - Ikome, Namondo Magdaline (My University, 2008)
Abstract Throughout history, many diseases have carried considerable stigma, including leprosy tuberculosis, cancer, mental illness and many STDs. Now HIV/AIDS is the topmost in the list of diseases that leads to devastating patient stigmatization. Despite international efforts to tackle HIV/AIDS, stigma and discrimination remain among the most poorly understood aspects of the epidemic. In the face of numerous intervention strategies, HIV/AIDS continues to spread and to pose a threat to the socio-economic transformation of South Africa. The broad objective of this study was to investigate how the stigmatisation of HIV-Positive women is made manifest and look at how successful the National Association of people living with HIV/AIDS (NAPWA) in South Africa has been in achieving their objectives and goals of changing the perceptions people have about HIV/AIDS and creating awareness about the debilitating effect stigmatisation has in the society, especially when it viciously targets HIV-positive women. A case study approach was used to examine the experiences of HIV/AIDS infected/affected women and NAPWA administrators. Methods used in the collection of data were self-administered questionnaires, participant observation and archival evidence in the form of documents. Through these methods, the study investigated ways in which the stigmatisation of HIV-positive women was made manifest, the role of NAPWA in fighting HIV/AIDS stigmatisation, how successful NAPWA has been in the fight against the stigmatisation of people infected and affected by HIV/AIDS in South Africa, challenges faced by NAPWA in the fight against HIV stigmatisation and discrimination, weaknesses of NAPWA and what impact all these have in the spread of HIV/AIDS. The research results show that HIV-positive women suffer stigmatisation and that; organisations of people living with HIV/AIDS (e.g. NAPWA-SA) play a major role in eradicating the stigma attached to HIV/AIDS. It also suggests that APWAs in effect help to reduce the spread of the disease and prolong the life span of those infected by it. All this not withstanding, the study also discovered that APWAs like NAPWA-SA need the support of government and stakeholders in South Africa to fully implement their strategies and programmes geared towards reducing stigma and the spread of HIV/AIDS.
Keywords: stigmatization; HIV-positive; women; Associations of people living with HIV/AIDS